2018
DOI: 10.1016/j.jas.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Species identification of ancient Lithuanian fish remains using collagen fingerprinting

Abstract: Morphological identification of ancient bone is often problematic due to heavy fragmentation that generally influences zooarchaeological assemblages. Fish bones are more taphonomically sensitive than those of other vertebrates as they are typically smaller and less biomineralised. Thus, taxonomic identification based on the preservation of morphological features is often extremely limited and can reduce or eliminate the usefulness of an assemblage for inferring taxon information. Currently, one of the most tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 54 publications
2
46
1
Order By: Relevance
“…Collagen fingerprinting has emerged as an important technique for archaeologists and Quaternary scientists, and this molecular tool is particularly useful for zooarchaeological identifications. Although several recent studies have demonstrated the value of this technique, many of these focus on terrestrial (Buckley et al 2016(Buckley et al , 2017 or marine mammals (Buckley et al 2014;Evans et al 2016;Hufthammer et al 2018), with comparatively limited attention, albeit growing, to fishes (Richter et al 2011;Harvey et al 2018). Our study is the first to use collagen fingerprinting for species identification of billfish, and points to the potential value of these data for helping understand prehistoric fisher encounter rates with various species and, if combined with archaeological evidence, ritual, and cultural variables.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Collagen fingerprinting has emerged as an important technique for archaeologists and Quaternary scientists, and this molecular tool is particularly useful for zooarchaeological identifications. Although several recent studies have demonstrated the value of this technique, many of these focus on terrestrial (Buckley et al 2016(Buckley et al , 2017 or marine mammals (Buckley et al 2014;Evans et al 2016;Hufthammer et al 2018), with comparatively limited attention, albeit growing, to fishes (Richter et al 2011;Harvey et al 2018). Our study is the first to use collagen fingerprinting for species identification of billfish, and points to the potential value of these data for helping understand prehistoric fisher encounter rates with various species and, if combined with archaeological evidence, ritual, and cultural variables.…”
Section: Discussionmentioning
confidence: 85%
“…1). Collagen fingerprinting (Buckley et al 2009) or ZooMS (short for Zooarchaeology by Mass Spectrometry; Buckley et al 2008) is an important and currently under-utilized technique that has been used to address a variety of zooarchaeological questions relating to species identification (e.g., Buckley and Kansa 2011;Buckley et al 2017a), including the discovery of the remains of extinct species (Buckley et al 2017b;Hufthammer et al 2018), but few studies have applied the technique to fish remains (Richter et al 2011;Harvey et al 2018). We demonstrate the value of ZooMS for analyzing archaeological fish bones and for addressing questions of broad significance to environmental archaeology and historical ecology, including the ecological versus cultural drivers of the Chumash billfish fishery.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen (I) is a slowly evolving biomolecule whereby approximately one amino acid substitution occurs every 1–8 Myr depending upon the vertebrate class, with fish collagen (I) yielding the greatest variation, followed closely by herpetofauna [33]. To date, no subspecies have been shown to differ in their collagen fingerprints, including in fishes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Initial work on the analysis of vertebrae shape has already shown to differentiate fish occupying different habitat niches (Samper Carro et al, 2018), and the method has potential to aid our identification methodologies further. Another fruitful avenue that may add to the range of tools for species determinations is ZooMS (Zooarchaeology by Mass Spectrometry) peptide fingerprinting (Harvey et al, 2018; Richter et al, 2011, 2020), but more species need to be added to the database of collagen spectra to be a useful technique in southeast Arabia.…”
Section: Discussionmentioning
confidence: 99%